Sintesis Triacetin dari Gliserol dan Asam Asetat dengan Katalis Zeolit Alam Termodifikasi - Semuel Gideon Rommy Kosegeran; Sanusi Gugule; Johny Zeth Lombok (Jurnal Kimia Fullerene, 2021)
Research has been conducted on the synthesis of triacetin from glycerol and acetate acid by the modify of natural zeolite catalyst with sulfuric acid 6N and followed by the characterization of the results of the reaction. Modified natural zeolite followed by an analysis of infrared spectrophotometry and x-ray diffraction (XRD). The characterization showed that modified natural zeolite has mordenite characteristics. The concentration of modified zeolite used is 3, 5, and 7% by weight of acetate acid as its reactant. Data processing used is one-way variation analysis and its characteristics seen in the physical-chemical test, followed by an analysis of gas chromatography-mass spectroscopic (GCMS) and infrared spectrophotometry. Based on the results of data processing, the concentrations of modified zeolite 3, 5, and 7% did not affect the yield of triacetin esterification reactions, the results respectively were 75,2881%, 71,9681%, and 69,0431%. The characterization results show that the physical-chemical properties of the reaction such as density, viscosity, and solubility are not following Standar Nasional Indonesia (SNI) of triacetin. The results of the GCMS analysis showed that there were two peaks with their respective fragments and the results of the infrared spectrophotometric analysis showed the presence of functional groups absorption for ester compounds.